1-MCP treatment affects peach fruit aroma metabolism as revealed by transcriptomics and metabolite analyses. (August 2019) - Cai, Hongfang; Han, Shuai; Jiang, Li; Yu, Mingliang; Ma, Ruijuan; Yu, Zhifang
Abstract: 1-methylcyclopropene (1-MCP) negatively affects peach aroma but the underlying molecular basis remains elusive. In this study, transcriptomics and metabolite analyses were carried out to investigate the regulatory mechanisms of 1-MCP on peach aroma from different standpoints: fatty acid (FA) metabolism, ethylene signal transduction and lipoxygenase/β-oxidation pathway during 20 °C storage. Results indicate that 1-MCP significantly postponed the ethylene climacteric peak appearance and reduced ethylene production through down-regulation of related biosynthesis and signal transduction genes including PpaSAMS1/2, PpaACS1/2, PpaACO1 together with PpaETR1/2, PpaERS1, PpaEIN4 and PpaCTR1. Decrease in the levels of FAs and PpaFADs was observed in treated fruit, except oleic acid and PpaFAD4/5, before day 5 of storage. In addition, 1-MCP-treated fruit also possessed higher levels of C6 aldehydes and alcohols and delayed the formation of volatile compounds characteristic of peach-like aroma by upregulation of PpaLOX1/2/3 and PpaHPL1 expression and down-regulation of PpaLOX5 expression. Our findings suggest that inhibition of peach-like volatiles and promotion of green-note volatiles by 1-MCP were associated with ethylene production and modulation of FA levels through transcriptional regulation. Graphical abstract: Unlabelled Image Highlights: RNA-Seq was first used to study the regulatory mechanism of 1-MCP on peach aroma. 1-MCP kept volatile pattern of unripe fruit and delayed peach-like aroma's formation. 1-MCP affected the formation of aroma by regulating pivotal enzyme genes.